Mathematical models for the apparent mass of the seated person exposed to fore-and-aft vibration - Abdul Jalil, Nawal Aswan (Federation of Engineering Institutions of Islamic Countries, 2006)
Four multi-degree-of-freedom linear lumped parameter models representing the seated human-body are developed. The optimum parameters for each model are derived from the median apparent mass of the back of ten male subjects previously reported. The fitted curves were obtained by fitting both the modulus and phase of the apparent mass data. All models showed good predictions of the apparent mass of the back between 0.25 and 10 Hz when compared to the experimental data. The height of the centre of gravity in models with rotational degree-of-freedom was fixed to the maximum of 1 m, measured from the pivot so as to give good fittings. It was found that the mass (M), spring (K) and damping (C) parameters obtained from fitting the models with the median apparent mass of the back of ten subjects showed better curve than when using median MKC obtained the individual responses. It is concluded that all models provides an apparent mass of the back similar to that of the human back, but it does not imply that the body moves in the same manner as the masses in these optimized multi-degree-of-freedom models.